Reading the Ideology of Salafi Da'wah: Media Technology Perspective - Sunaryanto, Sunaryanto; Rizal, Sofyan; Mulyono, Edi (Analisis: Jurnal Studi Keislaman, 2023)
Salafi expand da'wah using various media technologies. The use of various media as a means of Salafi da'wah shows that Salafis accept the presence of media technology well and use it to build an ideological da'wah movement. The discourse in this study was completed by qualitative research using a literature study approach, data analysis techniques using flow techniques with data reduction, data display, and formulating conclusions with data analysis. This study concludes that da'wah using media technology causes ideological conflicts with external parties, especially with traditional da'wah groups (eg Nahdlatul Ulama/ NU). The Salafi da'wah ideology can be accepted by the wider community because it uses new media as a place of work. New media for salafis is not only a place of preaching work but also a place to fight for their ideological authority. Salafi constructs ideological constructions through various digital images. The construction of Salafi ideology in digital images actually illustrates that the ideology of Salafi da'wah is not monolithic.